Model development of estimation of pointing accuracy when carrying out internal target designation and indication on samples of armored weapons - V. I. Kirnos; A. V. Zubar; V. P. Pivovarov (Омский научный вестник)
The article reveals a computing sequence at program implementation of the method of the internal target designation and indication for the samples of armored weapons. The authors describe the stages of the model development of an estimation of pointing accuracy on pixalized coordinates of the target image. They present the results of modeling in relation to the tank T-72B3, which is used in the army at present.